Between New Spheres of Influence: Ukraine's Geopolitical Misfortune. Issue 2 (3rd April 2018) - Ferguson, Iain
ABSTRACT: Contrary to the popular narrative of 'return', the spheres of influence that have destabilized Ukraine are not a throwback to the nineteenth century. They are something new. What makes them new is explained here in a story of a failed experiment to escape geopolitics in a region between the borders of an enlarged European Union (EU) and Russia. This project created a 'grey zone' of overlapping authority, jurisdiction and allegiance out of which new spheres of influence emerged. Ukraine's geopolitical misfortune was to be included into this 'grey zone'. The logic of this new narrative of the Ukraine crisis is worked out with reference to the literature on neo-medievalism – a political theory that develops a critique of supranational projects like European integration.